Perancangan dan Penerapan Sistem Penilaian Kinerja Karyawan pada PT. Rofenni Prima Jaya - Syaeful Anas Aklani; Jenry Winata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
PT. Rofenni Prima Jaya is a company engaged in land construction services and heavy equipment rental business that has been operating since 1994. The company's problems are insufficient attendance time and lack of employee discipline every month, which can be measured by monthly attendance in the form of employee permits that are delayed resulting in a decrease in productivity and quality. To help the company, an employee performance appraisal system was created. The method used in system development is using the waterfall method and also developing the system using the Hypertext Preprocessor, JavaScript, JQuery, and Bootstrap CSS programming languages, as well as using phpMyAdmin. The results of the system will provide an assessment form by doing one click on the Check List Form button in each period, assessment results reports, and assessment results reports per period. With this assessment system, employees can maintain the performance of employees to achieve the goals that have been targeted, as well as identify deficiencies in carrying out responsibilities.